High prevalence of renal salt wasting induced by haptoglobin-related protein without signal peptide is linked to new syndrome of salt wasting in Alzheimer disease - John K. Maesaka; Louis J. Imbriano; Candace Grant; Nobuyuki Miyawaki (The Korean Society of Nephrology, 2024)
The subject of hyponatremia is undergoing significant changes after developing a more pathophysiologic approach that is superior to the ineffective volume approach and can more effectively identify the different causes of hyponatremia. This new approach identified cerebral salt wasting (CSW) in 24 (38%) of 62 hyponatremic patients from the medical wards of the hospital with 21 showing no evidence of cerebral disease to support our proposal to change CSW to renal salt wasting (RSW). RSW had to be differentiated from the syndrome of inappropriate secretion of antidiuretic hormone (SIADH) because of diametrically opposite therapeutic goals of water-restricting water-logged patients with SIADH or administering salt water to volume-depleted patients with RSW. Both syndromes present with identical clinical parameters that require a difficult protocol to make such a differentiation possible. We describe rat clearance studies demonstrating natriuretic activity in the plasma of patients with neurosurgical and Alzheimer diseases (AD) and eventually identify the protein as haptoglobin-related protein without signal peptide, which can serve as a biomarker to simplify diagnosis of RSW and delivery of the proper management to improve clinical outcomes. We also discuss the introduction of a new syndrome of RSW in AD and its implications. The high prevalence of RSW and identification of the natriuretic factor have created debates over the existence of RSW with none questioning or addressing the pathophysiologic data that identified patients with RSW. We also discuss the potentially large group of patients with RSW who are normonatremic.